2012
DOI: 10.1159/000339556
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorder Comorbidity in Bipolar Disorder, Schizophrenia and Schizoaffective Disorder

Abstract: Background: Reported rates of comorbid anxiety disorders in psychotic and mood disorders vary widely among studies. Sampling and Methods: We used the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, fourth edition, to examine rates of comorbid anxiety disorders in patients with schizoaffective disorder (SZA; n = 153), bipolar I disorder (BP; n = 304) and schizophrenia (SZ; n = 174). Results: The rates of anxiety disorders in participants with SZA (30.1%), BP (22.4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 51 publications
2
17
0
1
Order By: Relevance
“…In epidemiological surveys, the lifetime comorbidity rates for any anxiety or related disorder among patients with bipolar disorder was 52% in Canada [43] and 60-75% in the US [1389,1399]. In a clinic population, the rate of anxiety and related disorders was 22% in patients with bipolar disorder, compared to 17% in patients with schizophrenia, and 30% in those with schizoaffective disorder [1400]. A meta-analysis of prevalence studies found that the rates of various anxiety disorders in patients with schizophrenia and related psychotic disorders ranged from 10-15% [1401].…”
Section: Anxiety With Comorbid Conditionsmentioning
confidence: 99%
“…In epidemiological surveys, the lifetime comorbidity rates for any anxiety or related disorder among patients with bipolar disorder was 52% in Canada [43] and 60-75% in the US [1389,1399]. In a clinic population, the rate of anxiety and related disorders was 22% in patients with bipolar disorder, compared to 17% in patients with schizophrenia, and 30% in those with schizoaffective disorder [1400]. A meta-analysis of prevalence studies found that the rates of various anxiety disorders in patients with schizophrenia and related psychotic disorders ranged from 10-15% [1401].…”
Section: Anxiety With Comorbid Conditionsmentioning
confidence: 99%
“…This is partially responsible for the varying prevalence rates among studies and the confl icting opinions between authors. Any anxiety disorder is reported to be present in 42-93 % of patients during lifetime and in almost 11-70 % cross-sectionally (Young et al 2013 ;Tamam and Ozpoyraz 2002 ;Altshuler et al 2010 ;Zutshi et al 2006 ;Simon et al 2004b ;Kawa et al 2005 ;Kessler et al 1997 ;Levander et al 2007 ;Nakagawa et al 2008 ;Goldstein and Levitt 2008 ;Schaffer et al 2006 ;Otto et al 2006 ;Nery-Fernandes et al 2009 ;Mantere et al 2006Mantere et al , 2010Henry et al 2003 ;Freeman et al 2002 ;Dittmann et al 2002 ;Das 2013 ;Cosoff and Hafner 1998 ;Ciapparelli et al 2007 ;Bellani et al 2012 ;McElroy et al 2001 ;Boylan et al 2004 ;Szadoczky et al 1998 ;Weber et al 2011 ;Azorin et al 2009 ). Up to half of these BD patients with comorbid anxiety manifest at least two anxiety disorders (Henry et al 2003 ).…”
Section: Comorbid Anxietymentioning
confidence: 99%
“…In BD patients, panic disorder is reported to have a cross-sectional prevalence of 2.3-62.5 % and a lifetime prevalence of 2.9-56.5 % (Vieta et al 2001 ;Schaffer et al 2006 ;Young et al 1993Young et al , 2013Tamam and Ozpoyraz 2002 ;Altshuler et al 2010 ;Zutshi et al 2006 ;Simon et al 2004b ;Kawa et al 2005 ;Kessler et al 1994Kessler et al , 1997Levander et al 2007 ;Nakagawa et al 2008 ;Goldstein and Levitt 2008 ;Rihmer et al 2001 ;Azorin et al 2009 ;Pini et al 1997Pini et al , 2003Otto et al 2006 ;Okan Ibiloglu and Caykoylu 2011 ;Mula et al 2008a ;Henry et al 2003 ;Dilsaver et al 1997Dilsaver et al , 2008Slama et al 2004 ;Dell'Osso et al 2011 ;Craig et al 2002 ;Cosoff and Hafner 1998 ;Ciapparelli et al 2007 ;Mantere et al 2006 ;McElroy et al 2001 ;Robins and Regier 1991 ;Chen and Dilsaver 1995 ;Bellani et al 2012 ;Boylan et al 2004 ;Coryell et al 2009 ;Szadoczky et al 1998 ). The phase of the disorder plays an important role; panic is virtually absent in purely manic patients and present in more than 80 % of mixed or depressive patients (Dilsaver and Chen 2003 ).…”
Section: Comorbid Panic Disordermentioning
confidence: 99%
“…Undifferentiated anxiety in schizophrenia may compound the morbidity and mortality in schizophrenia as syndromal anxiety does. Syndromal anxiety has been found to impact negatively on quality of life [10,11], functioning [11][12][13][14], overall psychopathology and the severity of comorbid medical conditions [15][16][17][18]. Increased rates of relapse, more frequent and longer duration of hospitalisations, poorer response to pharmacological treatments, substance abuse, negative attributional style, suicide and suicide attempts have been associated with anxiety in schizophrenia [19][20][21][22][23][24][25].…”
mentioning
confidence: 99%